Impacting Factors of Default Risk of Personal Housing Loans in China: Based on MCLP Model - Zhao, Li; He, Guangrui (International Journal of Global Economics and Management, 2024)
A large-scale default on personal housing loans will have a significant negative impact on the stability of the financial system and the smooth operation of the macro-economy. After the pandemic, preventing personal housing loan risks has become particularly important. Based on personal housing loans from commercial banks in China, a personal housing loan default risk model was constructed using the MCLP model, and the prediction results of the MCLP model were compared with those of the traditional logistic model to identify indicators that may affect default risk of personal housing loans. It was found that the MCLP had higher accuracy than the traditional logistic model. Empirical findings indicated that the education level, employment status, monthly household income, and census register of housing loan borrowers were primary factors influencing customer defaults.